Assessing Targeted Containment Policies to Fight COVID-19 - Ariadne Checo; Francesco Grigoli; Jose M. Mota (Global Labor Organization (GLO), 2021)
The large economic costs of full-blown lockdowns in response to COVID-19 outbreaks, coupled with heterogeneous mortality rates across age groups, led to question non-discriminatory containment mea- sures. In this paper we provide an assessment of the targeted approach to containment. We propose a SIR-macro model that allows for heterogeneous agents in terms of mortality rates and contact rates, and in which the government optimally bans people from working. We find that under a targeted pol- icy, the optimal containment reaches a larger portion of the population than under a blanket policy and is held in place for longer. Compared to a blanket policy, a targeted approach results in a smaller death count. Yet, it is not a panacea: the recession is larger under such approach as the containment policy applies to a larger fraction of people, remains in place for longer, and herd immunity is achieved later. Moreover, we find that increased interactions between low- and high-risk individuals effectively reduce the benefits of a targeted approach to containment.
Keywords: E10; H00; I10; 330; Optimal containment policies; COVID-19; heterogeneous agents; mortality rate; voluntary social distancing